The Pricing and Efficiency of Australian Treasury Bond Futures - Alex Frino; William Peng He; Andrew Lepone (Australasian Accounting, Business and Finance Journal, 2014)
This paper examines the efficiency of the Treasury Bond futures market in Australia. We provide a comprehensive explanation of the method used to price, and evaluate efficiency of the 3 and 10 Year Australian Treasury Bond Futures contracts, against underlying bond baskets. Results indicate that the futures contracts exhibit minimal variation from their theoretical value. The average mispricing equates to 1.96 basis points for 3 Year and 1.19 basis points for 10 Year government bond futures contracts. However, during some periods (including the financial crisis of 2008), the bond futures contracts exhibit greater mispricing. Consistent with prior literature, we find a decreasing pattern of mispricing towards expiry, with the futures contract yields and average forward yields of the underlying bonds converging towards expiry. Further analysis reveals that volatility and time to expiry exhibit a significant positive relationship with the absolute level of mispricing.
Keywords: Treasury bank futures; Market Microstructure